Vaccination of calves with yeast‐ and bacterial‐expressed paramyosin from the bovine lungworm Dictyocaulus viviparus. (December 2015) - Joekel, D.; Hinse, P.; Raulf, M. K.; Schicht, S.; Bäumer, W.; Werling, D.; Kremmer, E.; Strube, C.
Summary: Previously, vaccination of cattle with Escherichia coli ‐expressed bovine lungworm paramyosin (EcPMY) adjuvanted with Quil A resulted in considerable reduction in worm burden and larvae shedding (Strube et al ., 2015). To further evaluate the protective potential of PMY, cattle vaccination trials were performed using either E. coli ‐ (EcPMY) or Pichia pastoris ‐expressed PMY (PpPMY) with different adjuvants (Matrix‐Q ™ or Quil A). Combinations EcPMY+Matrix‐Q ™ (trial 1), PpPMY+Matrix‐Q ™ (trial 2) and PpPMY+Quil A (trial 3) were tested against challenge infections with 2000 Dictyocaulus viviparus larvae. Even though GM worm burden and larvae shedding was lower in almost all vaccinated groups, there were high variations between individuals hampering significant differences. However, in all vaccinated groups, lungworms were significantly shorter compared with those in controls. In vitro stimulation of peripheral blood mononuclear cells (PBMC) with recombinant (r)PMY revealed no significant proliferation following vaccinations or challenge infection. All vaccinated cattle showed a significant rise in specific antibodies, particularly IgG and its subclass IgG1, and detected the native lungworm PMY in immunoblots starting 2 weeks after the first vaccination. The use of a different rPMY‐adjuvant combination or combined vaccination with additional recombinant antigens might be a promising future approach towards a new vaccine against lungworms in cattle.